2014
DOI: 10.2337/db13-0778
|View full text |Cite
|
Sign up to set email alerts
|

The p75 Neurotrophin Receptor Is Required for the Major Loss of Sympathetic Nerves From Islets Under Autoimmune Attack

Abstract: Our goal was to determine the role of the p75 neurotrophin receptor (p75NTR) in the loss of islet sympathetic nerves that occurs during the autoimmune attack of the islet. The islets of transgenic (Tg) mice in which β-cells express a viral glycoprotein (GP) under the control of the insulin promotor (Ins2) were stained for neuropeptide Y before, during, and after virally induced autoimmune attack of the islet. Ins2-GPTg mice injected with lymphocytic choriomeningitis virus (LCMV) lost islet sympathetic nerves b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
42
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(44 citation statements)
references
References 37 publications
(59 reference statements)
2
42
0
Order By: Relevance
“…A more recently developed non-viral method of diabetes induction involves the administration of multiple, sequential, pharmacological agents which induce in the RIP-GP mouse immunological responses similar to those seen during the viral attack [21]. The loss of islet sympathetic nerves is approximately 80% using the viral method [22] and 60% using the non-viral method (Fig. 1).…”
Section: Characteristics Of Nerve Lossmentioning
confidence: 99%
See 4 more Smart Citations
“…A more recently developed non-viral method of diabetes induction involves the administration of multiple, sequential, pharmacological agents which induce in the RIP-GP mouse immunological responses similar to those seen during the viral attack [21]. The loss of islet sympathetic nerves is approximately 80% using the viral method [22] and 60% using the non-viral method (Fig. 1).…”
Section: Characteristics Of Nerve Lossmentioning
confidence: 99%
“…Even before diabetes onset, the minority of NOD islets that are heavily infiltrated have fewer sympathetic nerves than the majority of islets which are only sparsely infiltrated [20]. Likewise, in the RIP-GP mouse, there is no loss of islet sympathetic nerves before the islet is infiltrated, yet there is a major loss as soon as the islet becomes heavily infiltrated [22]. The implication of these correlational studies was confirmed by an interventional study: blocking the lymphocytic infiltration of the islet by the administration of complete Freund’s adjuvant to NOD mice prevented the loss of islet sympathetic nerves as well as the development of diabetes [20].…”
Section: Characteristics Of Nerve Lossmentioning
confidence: 99%
See 3 more Smart Citations